Design of melt-recyclable poly(ε-caprolactone)-based supramolecular shape-memory nanocomposites. Issue 48 (30th July 2018) - Pilate, Florence; Wen, Zhi-Bin; Khelifa, Farid; Hui, Yan; Delpierre, Sebastien; Dan, Luo; Mincheva, Rosica; Dubois, Philippe; Yang, Ke-Ke; Raquez, Jean-Marie
Abstract : Novel melt-recyclable poly(ε-caprolactone)/cellulose nanocrystals supramolecular nanocomposite networks with shape-memory behavior have been successfully constructed by playing with UPy chemistry. Abstract : A novel poly(epsilon-caprolactone) (PCL) supramolecular network exhibiting shape-memory behavior was successfully constructed with pendant UPy units that are highly able to dimerize. The dynamic network was obtained by a simple and versatile strategy consisting of chain-extension reaction between α, ω-dihydroxyoligoPCL and hydroxylated UPy units in the presence of hexamethylene diisocyanate as a coupling agent and further intermolecular dimerization of the UPy along the polyurethane backbone. 1 H NMR analyses confirmed the dynamic features of the system, and DMTA in tensile mode was investigated to assess the SMP properties. Recyclability was also assessed by taking advantage of these supramolecular networks. Further addition of cellulose nanocrystals into the polymer network enabled adjustment of the extent of the net-points and therefore the SMP features. As confirmed by dispersion tests in solution and SEM observations, these bio-based nanofillers were homogeneously distributed in the network via supramolecular interaction between the hydroxyl groups present on their surface and UPy moieties along the polyurethane backbone. Thus, the here developed nanomaterials might reveal applicability in areas where a combination of SMP and biocompatibility is needed.